The port landscape of Malacca, as perceived and constructed by the Portuguese in the early 16th century - García Cuéllar, Miriam Alejandra (2025)
This article seeks to analyze the perceptions and transformations that were generated around the port landscape of the city of Malacca,  because of the first Portuguese incursions, which contacted Malay societies in the 16th century, attacking and capturing the city in 1511. In general, this work aims to study how perceptions of the port city were constructed and transformed by external (Portuguese) societies. Thus, this study explores the transformations experienced by the city of Malacca due to the Portuguese conquest, which resulted in the transformation of that space from a city port with a hinterland to an entrepôt without a hinterland.